ANALISIS SWOT, IFE, EFE DAN MATRIKS QSPM DALAM STRATEGI PENGEMBANGAN BISNIS RS XYZ - Stevani Novita (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
XYZ Hospital is a private general hospital, class C, with 100 beds which will serve the community in Bandung and its surroundings. Global challenges and the emergence of a large number of new hospitals have resulted in high competitive intensity for the health services industry. Hospitals must make strategic plans to achieve competitive advantage, maintain survival and anticipate dynamic changes in achieving organizational goals. Strengths, weaknesses, opportunities and threats (SWOT) analysis and IFE, EFE, TOWS and QSPM matrix analysis techniques can be used in creating appropriate hospital management strategies. This research used descriptive qualitative methods and data was collected from discussions with hospital management, literature review of published documents and internal hospital management data. The objectives of this research are (1) to identify external and internal factors, (2) to formulate alternative business development strategies, (3) to determine business development strategy priorities. The results show that XYZ hospital must implement an aggressive strategy. The alternative strategy used is SO (using strength to create opportunities), with a priority strategy to increase hospital promotion to companies and agencies that have not yet collaborated.